2004
DOI: 10.1002/esp.1067
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns of runoff and erosion responses to simulated rainfall in a badland area in Mediterranean mountain conditions (Vallcebre, southeastern Pyrenees)

Abstract: Regolith surface characteristics and response were examined over a three-year period in a badland area in a Mediterranean middle-mountain zone near Vallcebre (Eastern Pyrenees). Preliminary work carried out in this area indicated clear seasonal patterns of regolith properties driven by frost heaving in winter and crusting and erosion in the rest of the year. Rainfall simulations were performed with a small portable nozzle simulator in order to study seasonal changes in runoff generation, erosion rates and rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 26 publications
4
45
0
2
Order By: Relevance
“…Temporal patterns observed in the current study were similar to that reported by Regüés and Gallart (2004) at Vallcebre, southeast Pyrenees. In that study, sediment concentrations in runoff samples were higher in spring and autumn than in winter and summer, and sediment detachability by splash was higher in spring and autumn than in winter and summer.…”
Section: Due To Different K Fs Values For the Different Land Uses Rusupporting
confidence: 89%
“…Temporal patterns observed in the current study were similar to that reported by Regüés and Gallart (2004) at Vallcebre, southeast Pyrenees. In that study, sediment concentrations in runoff samples were higher in spring and autumn than in winter and summer, and sediment detachability by splash was higher in spring and autumn than in winter and summer.…”
Section: Due To Different K Fs Values For the Different Land Uses Rusupporting
confidence: 89%
“…Low infiltration rates are recorded in bare soil due to the typical surface sealing in badlands (Regüés and Gallart, 2004;Nadal-Romero and Regüés, 2009), which agreed with the properties of soils developed on marls (Badía et al, 2015). Slope aspect has often been identified as a factor that determines soil degradation, vegetation cover and infiltration rates (Seeger et al, 2006;Regüés et al, 2012;Robertson and Sharp, 2015), especially in areas affected by farmland abandonment (Lana-Renault, 2009).…”
Section: Effect Of Vegetation Coversupporting
confidence: 52%
“…Nadal- , based on field evidence and laboratory work, suggested that in these badland morphologies shallow landslides and small mudflows commonly occur during prolonged rainfall events. These erosion processes produced the development of fans at the base of slopes and near the main channels, processes also observed in different badland morphologies (Balasch, 1998;Regüés and Gallart, 2004;Desir and Marín, 2007). It is also remarkable that during summer, convective storms of high intensity and short duration overcome infiltration capacity and generate intense concentrated runoff.…”
Section: Geomorphological Dynamicsmentioning
confidence: 99%